MANAJEMEN KURIKULUM DALAM PENGEMBANGAN KARAKTER DAN KETERAMPILAN SISWA DI MADARASAH TSANAWIYAH AN NAJAH PEKANBARU - Elfita Wicahya; Dian Nikmatus Sholikha; Yona Afriyani (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of curriculum management in developing students’ character and skills using the POAC (Planning, Organizing, Actuating, Controlling) approach, as well as to identify supporting and inhibiting factors in its implementation. The research employed a descriptive qualitative approach with key informants including the principal, curriculum team, teachers, and educational staff. Data were collected through semi-structured interviews, document observation, and participatory observation of academic and extracurricular activities. The findings indicate that the planning stage emphasizes the development of success indicators integrating religious values, character, and practical skills; the organizing stage ensures task distribution, coordination, and resource allocation are efficient; the actuating stage combines academic activities, character development, and skill enhancement through varied learning strategies; and the controlling stage evaluates the achievement of indicators holistically and serves as a basis for curriculum improvement. Supporting factors include visionary leadership, active teacher involvement, adequate facilities, and parental participation, while inhibiting factors involve limited teaching staff, financial constraints, students’ family conditions, and restricted access to facilities or skill training. This study confirms that effective and integrated curriculum management can produce graduates who are intelligent, religious, and skilled, in accordance with the institution’s vision and mission.